UNIT 4.19 Ribosomal RNA Depletion for Efficient Use of RNA‐Seq Capacity. Issue 1 (July 2013) - O'Neil, Dominic; Glowatz, Heike; Schlumpberger, Martin
Abstract: Ribosomal RNA (rRNA) is the most highly abundant component of RNA, comprising the majority (>80% to 90%) of the molecules present in a total RNA sample. Depletion of this rRNA fraction is desirable prior to performing an RNA‐seq reaction, so that sequencing capacity can be focused on more informative parts of the transcriptome. This unit describes an rRNA depletion method based on selective hybridization of oligonucleotides to rRNA, recognition with a hybrid‐specific antibody, and removal of the antibody‐hybrid complex on magnetic beads. Curr. Protoc. Mol. Biol. 103:4.19.1–4.19.8. © 2013 by John Wiley & Sons, Inc.